Analysis of Merchandise Inventory Accounting Treatment Based on SAK EMKM at UMKM Ayakh Ugan Baturaja - UTAMI, Amanda Dwi; ZULKIFLI, Zulkifli; YULINA , Bainil (Journal of Governance, Taxation and Auditing, 2025)
This study examines the recording and valuation of merchandise inventory at UMKM Ayakh Ugan Baturaja. Data were obtained through interviews and company documentation. The findings reveal that the enterprise has not implemented an inventory recording system or valuation method in line with generally accepted accounting standards. Inventory transactions are recorded simply in goods-in and goods-out logs, without a formal system, and the ending inventory is valued by multiplying the last purchase price by the remaining units, which does not reflect the actual financial position. Comparative calculations using FIFO (First In, First Out) and Weighted Average methods show that the gross profit reported by the company is higher than the results obtained using these standard methods. The study recommends adopting a perpetual inventory system to monitor ending inventory in real time and applying the FIFO method for inventory valuation, as it is simple, practical, and produces a higher gross profit. Implementing these recommendations will improve the accuracy and reliability of financial reporting for the enterprise.